The The Effect of Profitability, Leverage, Liquidity, Company Growth, Previous Year Audit Opinion, and Company Size on Opinion of Going Concern - Akhmad Afnan; Alfina Syahara Putri (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2025)
The industrial sector is highly vulnerable to economic and policy changes, making it a strong candidate for further study. The industrial sector also contributes to the national economy, so the operational continuity of companies in the industrial sector has a broad impact on overall economic stability. The second reason for choosing companies in the industrial sector is that this sector is highly dependent on external factors, including the company and the economy, so it faces risks to business continuity. Industrial companies must be more reliable in developing strategies to survive in uncertain conditions. The industrial enterprises listed on the IDX during the 2021–2023 study period served as the study's population. Logistic regression was the study model that was employed. Based on the testing and the explanation, these research results indicate that no single ratio—whether leverage, liquidity, size, or growth—is decisive. Ultimately, the listed ratios are merely diagnostic indicators that prompt deeper audit procedures; the failure to secure financing or present a viable, credible survival strategy is what leads to the issuance of an opinion. A research limitation is that the financial ratios used do not reflect the overall condition; they only describe the economic condition at a single point in time. Meanwhile, many external conditions, especially those related to macroeconomics, are more uncertain and less controllable by the company, such as foreign exchange rates, raw material prices, inflation, political conditions, and broader economic conditions.